Ultrasonography in acute appendicitis - Prasad, V Natraj; Chhetri, Pramod Kumar (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: This study was undertaken to establish the Ultrasonographic (USG) findings in acute appendicitis and to establish the accuracy of USG in the diagnosis of acute appendicitis. Materials & Methods: One hundred patients who presented to the emergency department with a clinical diagnosis of acute appendicitis were subjected to USG. USG findings of those patients suggestive of acute appendicitis were noted. The decision to operate for appendicitis was made on the surgeon's final clinical impression after correlating with USG findings. Histopathological examination of the appendicectomy specimen was taken as the gold standard for the diagnosis of acute appendicitis. Results: USG diagnosis of acute appendicitis is based on a combination of sonographic features. The findings of an aperistaltic tubular structure arising from the caecum with a target appearance on cross section, outer diameter of > 6 mm, mural wall thickness > 3 mm, and probe tenderness over the visualized appendix should prompt the diagnosis in the appropriate clinical settings. The visualization of appendicolith is associated with higher rate of perforation and the visualization of fluid with internal echoes in acute appendicitis could suggest abscess formation. Conclusion: USG is a very useful and essential modality in the diagnosis of acute appendicitis with a sensitivity of 93.93%, specificity of 100%, PPV of 100%, NPV of 89.47% and an overall accuracy of 96% in the diagnosis of acute appendicitis.